Association of statin use and risk for severe headache or migraine by serum vitamin D status: A cross-sectional population-based study. (August 2015) - Buettner, Catherine; Burstein, Rami
Objective: The objective of this article is to evaluate whether statin use and vitamin D status is associated with severe headache or migraine in a nationally representative sample. Methods: We conducted a cross-sectional study of US individuals aged ≥40 years for whom information on statin use, serum 25-hydroxy vitamin D (25(OH)D), and self-reported severe headache or migraine had been collected. We calculated prevalence estimates of headache according to statin and 25(OH)D, and conducted adjusted logistic regression analyses stratified by the median 25(OH)D (≤57 and >57 nmol/l). Results: Among 5938 participants, multivariable-adjusted logistic regression showed that statin use was significantly associated with a lower prevalence of severe headache or migraine (OR 0.67; 95% CI 0.46, 0.98, p  = 0.04). We found a significant interaction between statin use and 25(OH)D with the prevalence of severe headache or migraine ( p for interaction = 0.005). Among participants who had serum 25(OH)D > 57 nmol/l, statin use was associated with a multivariable-adjusted odds ratio of 0.48 (95% CI 0.32, 0.71, p  = 0.001) for having severe headache or migraine. Among those with 25(OH)D ≤ 57 nmol/l, no significant association was observed between statin use and severe headache or migraine. Conclusion: Statin use in those with higher serum vitamin D levels is significantly associated with lower odds of having severe headache or migraine.